Cover Image, Volume 50, Issue 3. Issue 3 (2nd June 2019) - Bonnet, Guillaume; Batisse, Cindy; Peyron, Marie‐Agnès; Nicolas, Emmanuel; Hennequin, Martine
Abstract : The cover image is based on the Review Paper Which variables should be controlled when measuring the granulometry of a chewed bolus? A systematic review by Guillaume Bonnet et al., DOI 10.1111/jtxs.12376 .